2012
DOI: 10.1371/journal.pntd.0001573
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genetic Diversity, Unique Population Structure and Evidence of Genetic Exchange in the Sexually Transmitted Parasite Trichomonas vaginalis

Abstract: Background Trichomonas vaginalis is the causative agent of human trichomoniasis, the most common non-viral sexually transmitted infection world-wide. Despite its prevalence, little is known about the genetic diversity and population structure of this haploid parasite due to the lack of appropriate tools. The development of a panel of microsatellite makers and SNPs from mining the parasite's genome sequence has paved the way to a global analysis of the genetic structure of the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
148
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(171 citation statements)
references
References 63 publications
21
148
1
1
Order By: Relevance
“…Microsatellite markers have been used to characterize the genetic diversity and population structure of several protozoan pathogens, including Leishmania tropica, Trypanosoma cruzi, Trypanosoma brucei gambiense, Plasmodium species, and Toxoplasma gondii (2,6,8,12,29,30,44,53,55). Recently, the usefulness of microsatellite makers to assess the genetic diversity and transmission of T. vaginalis has also been demonstrated (10,11,46). However, the generally high mutation rate of microsatellite markers can cause homoplasy, which may distort the inferred evolutionary history of a species (19).…”
mentioning
confidence: 99%
“…Microsatellite markers have been used to characterize the genetic diversity and population structure of several protozoan pathogens, including Leishmania tropica, Trypanosoma cruzi, Trypanosoma brucei gambiense, Plasmodium species, and Toxoplasma gondii (2,6,8,12,29,30,44,53,55). Recently, the usefulness of microsatellite makers to assess the genetic diversity and transmission of T. vaginalis has also been demonstrated (10,11,46). However, the generally high mutation rate of microsatellite markers can cause homoplasy, which may distort the inferred evolutionary history of a species (19).…”
mentioning
confidence: 99%
“…These studies had been done on the genotype of T. vaginalis and the relationship between its genotype and the clinical presentation of trichomoniasis, including metronidazole susceptibility, the presence of T. vaginalis virus (TVV) and Mycoplasma hominis (6)(7)(8)(9). In this study, all the samples were collected from Xinjiang and the low Our results demonstrated that the genetic diversity of Chinese T. vaginalis isolates was associated with geographic distance based on the 18S ribosomal RNA gene.…”
Section: Discussionmentioning
confidence: 76%
“…Several T. vaginalis sequences have been reported to date, and most of the 18S gene sequences have been reported in Chinese and Philippine studies (17)(18)(19). Previous studies indicate a relationship between T. vaginalis genotype and the clinical presentation of trichomoniasis (7,20,21). In this study, a distancebased network was constructed with three large clusters and many branches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations